Clofarabine for Lymphodepletion Before CAR-T-Cell Infusion: A Brief Case Report. Issue 4 (22nd May 2023) - Foti, Alycia; Stein, Dylan; Seidel, Drew; Levine, Jennifer; Hijiya, Nobuko; Williams, Olatundun; George, Diane; Bhatia, Monica; Satwani, Prakash
Abstract : Given the shortage of fludarabine, alternative preparative lymphodepleting regimens for CAR-T-cell therapy need to be identified. We present a case of relapsed/refractory B-cell acute lymphoblastic leukemia requiring multiple lines of salvage therapy with persistent extensive disease, who underwent lymphodepletion with clofarabine and cyclophosphamide before tisagenlecleucel CD19+ CAR-T-cell infusion with eventual remission. We offer evidence of clofarabine's activity against B-cell acute lymphoblastic leukemia in combination with tisagenlecleucel therapy. In this patient, clofarabine did not decrease CAR-T-cell effectiveness, supported by presence of cytokine release syndrome and ultimate minimal residual disease negativity both on flow cytometry and next-generation sequencing.